Efforts to Improve the Quality of Concrete Reinforcement Steel Tensile Testing Laboratory Services of PT XXI to Customer Satisfaction Using Service Quality and Importance Performance Analysis Methods - Mustikawati, Rofiqoh (Jurnal Inovisi (Teknik Industri), 2025)
This research aims to determine the quality of service of the PT. Concrete Reinforcement Steel Tensile Testing Laboratory. XXI towards customer satisfaction through the application of service quality and importance performance analysis methods. Steel testing laboratories play an important role in ensuring the quality and safety of materials used in various construction and industrial projects. Through the Servqual method approach, we can measure the gap between customer expectations and perceptions using five main dimensions, namely tangibles, reliability, responsiveness, assurance and empathy.